Management of recurrent inflammatory choroidal neovascular membrane secondary to Vogt-Koyanagi-Harada syndrome, using combined intravitreal injection of bevacizumab and triamcinolone acetate - Pai, Sivakami A (Medknow Publications & Media Pvt Ltd, 2012)
The purpose of this report is to evaluate the efficacy and safety of combined intravitreal injection of bevacizumab and intravitreal triamcinolone acetonide (IVTA) for recurrent inflammatory choroidal neovascular membrane (CNVM). It was a prospective interventional study of a young female, who was a known case of Vogt-Koyanagi-Harada syndrome. She presented with an inflammatory choroidal neovascualar membrane and signs of panuveitis in the right eye. She underwent a complete ophthalmic examination. She was given intravitreal injection of bevacizumab and IVTA at different sites. There was complete regression of CNVM and ocular inflammation within a week. After six months, she had recurrence of CNVM in the same eye, which was treated similarly. There was a complete resolution of CNVM and ocular inflammation after the combination therapy and systemic steroids, until one year of follow-up. No serious systemic or ocular adverse events were noted. Combination therapy appears to be an effective and safe method in the management of recurrent inflammatory CNVM.